JUMLAH LEUKOSIT DAN DERAJAT KLINIS PENDERITA INFEKSI DENGUE DI RSUD DR. H. ABDUL MOELOEK LAMPUNG: Number of Leukosites and Clinical Degree of Dengue Infection Patients at Dr. H. Abdul Moeloek Lampung - Hidayat; Rusmini, Hetti; Prasetia , Toni; Setiawan, Henri (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2021)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus transmitted by mosquitoes. Hematological abnormalities in the form of a decrease in the number of leukocytes which are influenced by the clinical degree due to stress on the bone marrow can occur in cases of DHF. The decrease or increase in the number of leukocytes was thought to be related to the clinical degree of DHF in previous studies. This study aimed to determine the relationship between the number of leukocytes and the clinical degree in patients with dengue infection. This study used an observational analytic method with a cross-sectional approach. The population consisted of 39 patients with dengue infection. The data on the results of the examination of the number of leukocytes and the clinical degree were obtained from medical record documents. Data analysis was performed using the Spearman correlation test. 39 study subjects suffering from dengue infection consisting of clinical degrees I (30.8%), II (61.5%), and III (7.7%). The leukocyte count was between 4,000-10,000/µL (59%) and the leukocyte count <4,000/µL (41%). The mean number of leukocytes at clinical grade I was 4.183/µL, at clinical grade II was 4.754/µL and clinical-grade III was 6.100/µL. The results of statistical tests with the Spearman correlation test obtained the value of r = -0.121 and the value of p = 0.462 (p> 0.05). There was no significant relationship between the leukocyte count and the clinical degree of dengue infection. Future researchers are expected to increase the number of research samples so that they can get all clinical degrees of DHF.